Free Triiodothyronine and Cholesterol Levels in Euthyroid Elderly T2DM Patients. (3rd September 2012) - Strollo, F.; Carucci, I.; Morè, M.; Marico, G.; Strollo, G.; Masini, M. A.; Gentile, S.
Abstract : Thyroid function regulates lipid metabolism. Despite the fact that T2DM is more prevalent in the elderly, often associates with thyroid dysfunction and increases cardiovascular risk both per se and via high TC and LDL-C levels, the association of the latter with FT3 and FT4 levels has not yet been fully investigated in T2DM. While trying to fill this gap in 296 elderly outpatients with T2DM, we found that TC and LDL-C correlated negatively with FT4 and positively with FT3 . When divided according to treatment by oral hypoglycaemic agents (OHA) and insulin (IT), they reacted differently with respect to investigated associations: in the OHA's TC and LDL-C correlated negatively with FT4 and showed no association with FT3, whereas, in the IT's TC and LDL-C correlated positively with FT3 and negatively with FT4 . When controlled for possible confounding factors, these associations did not change in the IT's but were missing in the OHA's. Recent literature reports upon complex hypothalamic and peripheral interactions between T2DM and thyroid, and suggests T3 to enhance cholesterol synthesis and to have a role in insulin resistance states. Further investigations are needed to understand the intimate mechanisms of lipid metabolism in T2DM with respect to thyroid function.